The Use of Interactive E-Books in Increasing Elementary School Students’ Reading Interest: A Literature Review - ANAM, ACH. KHOIRIL; Kusumawati , Wiladhatin Ira; Andini, Laili Firda; Lillah, Fadl; Susilawati, Samsul (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
Reading interest among elementary school students in Indonesia is still low, which is a significant challenge in efforts to improve the quality of basic education. With the advancement of digital technology, interactive e-books have emerged as a new, innovative choice in a fun and interesting learning process. This study is a literature review that aims to see the use of interactive e-books in increasing reading interest among elementary school students. The method used is a literature study that examines various scientific articles, journals, and related publications published in the last five years. The findings of the study indicate that interactive e-books, which are equipped with multimedia elements such as animation, sound, and interactivity, can trigger students’ interest in reading. In addition, the use of interactive e-books also facilitates independent learning and improves understanding of reading content. In conclusion, interactive e-books have significant potential as an effective learning tool to increase reading interest in elementary school students, especially if supported by the right teaching strategies.